Marco jurídico y regulatorio del servicio público domiciliario de gas licuado de petróleo - Álvarez, Carlos Yezid Rozo (Tecnogestión: Una mirada al ambiente, 2006)
The Liquefied Gas of the Petroleum (GLP); energy clean and to the onethat many utilities can be given it doesn't present the necessary consistencyin spite of being regulated in the Law of 142 of 1994; it is continuedwith studies of the regulatory mark without leaving clear the terms thatit allows by means of it to arrive to the population of but low resourceswith efficiency and quality. The informality like it is continued managingthe sector without place to doubts he/she has not stopped to weighin the objective of structuring a regulatory mark that a long term modelallows. It is clear that the offer of the service is bound to the existenceof hydrocarbons and I eat the curve well it is known he/she comes in agradual descent, reason for which the intervention of the state in a deepand concrete way is valuable in these moments that the sector lives. Asrelating point it should be kept in mind the gradual increase that one comesdeveloping in the emergence of plants pack but the cober up of usershe is not reflected; in the same way and consequently the capture of newmarkets is not representative.